Throughput dan Dwelling Time pada Yard Occupancy Ratio Pelabuhan Sunda Kelapa - Muhammad Riza Affiat; Fahri Fadli; Lut Mafrudoh (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
Sunda Kelapa Harbor as a branch of PT. PELINDO II, which is located in North Jakarta and is one of the ports where cargo ships berthed in Jakarta apart from Tanjung Priok port. Along with the development of the pattern of transporting goods using containers, PT IPC Sunda Kelapa Port provides services to containers by providing container stacking field facilities for loading and unloading, stuffing and stripping. This activity will provide an overview of the conditions of Throughput, Dwelling Time and Yard Occupancy Ratio. And these three elements will be the object of this research. The research objective was to determine how much influence the Throughput and Dwelling Time have on the Yard Occupancy Ratio. The research analysis method is Linear Regression analysis.The results of the analysis show that there is a significant influence between Throughput, Dwelling Time, on the Yard Occupancy Ratio.